Multipoint boundary-value problems with pulse effects - Karandzhulov, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
By using pseudoinverse matrices, we establish conditions for the existence and uniqueness of solutions of linear and weakly linear boundary-value problems for ordinary differential equations with pulse action. We consider the case where the dimension of a differential system does not coincide with the dimension of the boundary conditions.